Mathematics Is Scary: Efforts To Improve Junior High School Students' Perceptions of Mathematics Lessons Through Mathematics Games - Anjariyah, Deka; Feriyanto, F; Mursalin, M; Perbowo, Krisna Satrio (SAINTIS Publishing, 2024)
Mathematics is often perceived as a challenging and intimidating subject, especially at the junior high school level. This study aims to examine the impact of mathematical games on improving students' perceptions of mathematics. A pre-experimental design with a one-group pretest-posttest was utilized, involving 121 junior high school students aged 13–14 years. Students' perceptions were measured using a validated questionnaire before and after the intervention, and the data were analyzed using a paired sample t-test. Results revealed a significant increase in students' perceptions, as indicated by a p-value of 0.00116593×10−33, which p-value is smaller than the threshold of 0.05. The findings confirm that mathematical games effectively shift students' perceptions of mathematics from negative to positive. This research underscores the importance of innovative teaching methods, such as game-based learning, in creating engaging and supportive learning environments that foster positive attitudes toward mathematics.